In-vitro effect of some plant extracts on Buffalo leech, Hirudinaria manillensis - BAM, JOKEN; ISLAM, S; BHATTACHARYA, D; DEKA, D K; KALITA, D J; SHARMA, R K; PATHAK, PALLABI; MAITI, S; BERA, A K; DEB, S M (The Indian Journal of Animal Sciences, 2016)
The study was conducted to find out the anti-leech effect of 5 indigenously used plant species on Hirudinaria manillensis. Aqueous and methanolic extracts of Nicotiana spp., Zanthoxylum alatum, Solanum khasianum, Cucumis sativus and Lasia spinosa were prepared. The experiment was designed to evaluate 3 concentrations of aqueous (@5,000, 2,500 and 1,000 µg/ml) and methanolic extracts (@ 500, 100 and 50 µg/ml) of all the plants along with levamisole (83 µg/ml) as standard and distilled water as control. The leeches were treated with the determined concentration of extract/standard and the death time (min) was recorded up to 720 min. The aqueous extract of Nicotiana spp. and Z. alatum showed best anti-leech effect with mean death time ranging from 2.11±0.11 to 5.33±0.47 min and comparable result with the standard at 83 µg/ml concentration. The methanolic extracts of Z. alatum at all the concentrations and Nicotiana spp. and S. khasianum at 500 µg/ml showed no significantly different effect with levamisole standard. The methanolic extract of Z. alatum exhibited best hirudinicidal effect (10.56±2.69 min) against H. manillensis. Aqueous extract of S. khasianum and both aqueous and methanolic extracts C. sativus and spinosa showed no killing effect on H. manillensis at all the concentrations. It was concluded that among the 5 plant species, Nicotiana spp., Z. alatum and S. khasianum were effective against H. manillensis.